A genomic amplification affecting a carboxylesterase gene cluster confers organophosphate resistance in the mosquito Aedes aegypti: From genomic characterization to high‐throughput field detection. (16th February 2021) - Cattel, Julien; Haberkorn, Chloé; Laporte, Fréderic; Gaude, Thierry; Cumer, Tristan; Renaud, Julien; Sutherland, Ian W.; Hertz, Jeffrey C.; Bonneville, Jean‐Marc; Arnaud, Victor; Fustec, Bénédicte; Boyer, Sébastien; et al.
Abstract: By altering gene expression and creating paralogs, genomic amplifications represent a key component of short‐term adaptive processes. In insects, the use of insecticides can select gene amplifications causing an increased expression of detoxification enzymes, supporting the usefulness of these DNA markers for monitoring the dynamics of resistance alleles in the field. In this context, the present study aims to characterize a genomic amplification event associated with resistance to organophosphate insecticides in the mosquito Aedes aegypti and to develop a molecular assay to monitor the associated resistance alleles in the field. An experimental evolution experiment using a composite population from Laos supported the association between the over‐transcription of multiple contiguous carboxylesterase genes on chromosome 2 and resistance to multiple organophosphate insecticides. Combining whole genome sequencing and qPCR on specific genes confirmed the presence of a ~100‐Kb amplification spanning at least five carboxylesterase genes at this locus with the co‐existence of multiple structural duplication haplotypes. Field data confirmed their circulation in South‐East Asia and revealed high copy number polymorphism among and within populations suggesting a trade‐off between this resistance mechanism and associated fitness costs. A dual‐color multiplex TaqMan assay allowing the rapid detection and copy number quantification of this amplification event in Ae. aegypti was developed and validated on field populations. The routine use of this novel assay will improve the tracking of resistance alleles in this major arbovirus vector.